Heroism and Its Stages Depicted in J.K. Rowling's The Christmas Pig - Al Faqih, Alif Firdhi (English Literature Study Program, 2022)
This study aimed to discuss Jack's hero's journey stages and how he encountered obstacles in The Christmas Pig. This study was categorized into literary criticism using a psychological approach by applying Campbell's hero's journey theory (2004) and supported by Allison & Goethals' theory of obstacles (2011) in the hero's journey. The data were taken from words, phrases, sentences, and paragraphs in the novel The Christmas Pig by J.K. Rowling. The data were identified and interpreted, and then the conclusion was drawn. There were two results from this study. First, Jack passed all seventeen stages of the hero's adventure stages involving the call to adventure, refusal of the call, supernatural aid, the crossing of the first threshold, belly of the whale, the road of trials, the meeting with the goddess, woman as the temptress, atonement with the father, apotheosis, the ultimate boon, refusal of the return, the magic flight, rescue from without, the crossing of the return threshold, master of the two worlds, and freedom to live. Second, Jack encountered the obstacles by getting help from the allies, using his intelligence, being tough and patient, strong determined, and optimistic. In summary, Jack's hero's journey was completed, but it was not easy and full of obstacles. The researcher suggested further researchers to analyze The Christmas Pig by applying post-modernism, structuralism, or symbolism and analyzing different literary works using Campbell's hero's journey theory.